إشكالات التّعريف في المعاجم العربية"قاموس الوافر وجيز أنموذجاً - شيباني, محمد (جامعة الوادي - University of Eloued, 2023)
الملخص: لازالت إشكالية تعريف المداخل المعجمية تُطرح بقوّة في معاجمنا العربية،إذ من المنتظر أن يدرك صانع المعجم حاجة مستعمل ومتعلم اللّغة المتمثلة عموما في الوصول بكل سهولة ويسر إلى كل ما يرومه من معاني ودلالات. ولم يستطع مؤلفو المعاجم المدرسية تجاوز تلك العقبة خاصة وأنّ هذا النّوع من المعاجم موّجه إلى فئة خاصة هي فئة المتعلمين،ومن ثم فالاشكالية ازدادت حدّة. انطلاقا من هذ الطّرح اخترنا معجم(وافر وجيز) من خلال رصد مثالب التّعريف حيث ألفينا فيه أنواعا كثيرة من التّعريف أدت إلى إبهام المداخل أكثر من توضيحها وشرحها. الكلمات المفتاحية: التّعريف؛ المعجم المدرسي؛ التّأليف المعجمي؛ المعاجم العربية؛ المدخل المعجمي. Abstract:The problem of defining lexical entries is still strongly posed in our Arabic dictionaries, as it is expected that the dictionary maker realizes the need of the language user and learner, which is generally represented in fast accessing easily to all the meanings and connotations he wants. The authors of school dictionaries were unable to overcome that obstacle, especially since this type of dictionaries is directed to a special category, i.e. the learners category, and therefore the problem has severely increased in. Based on this proposition, we chose the "Alwafir Wadjiz" dictionary by observing the defects of the definition, where we found many types of definitions that led to the ambiguity of the entrances rather than their clarification and explanation. key words:definition; school dictionary; lexical writing; Arabic dictionaries; lexicon entry.
Article
Keywords: المعجم المدرسي ; التأليف المعجمي ; المعاجم العربية ; المدخل المعجمي